2011
DOI: 10.2519/jospt.2011.3547
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Modified NFL Combine Testing to Identify Functional Deficits in Athletes Following ACL Reconstruction

Abstract: STUDY DESIGN Case control. OBJECTIVES To use modified NFL Combine testing methodology to test for functional deficits in athletes following anterior cruciate ligament (ACL) reconstruction following return to sport. BACKGROUND There is a need to develop objective, performance-based, on-field assessment methods designed to identify potential lower extremity performance deficits and related impairments in this population. METHODS Eighteen patients (mean ± SD age, 16.9 ± 2.1 years; height, 170.0 ± 8.7 cm; bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
195
1
16

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 200 publications
(222 citation statements)
references
References 47 publications
10
195
1
16
Order By: Relevance
“…This test not only measures neuromuscular control but has also been correlated to quadriceps and hip strength. 9,10 Particularly the anterior reach portion demonstrates high activation of the vastus medialis and lateralis. 11 The YBT-LQ has not been studied preoperatively in an ACL-R population to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This test not only measures neuromuscular control but has also been correlated to quadriceps and hip strength. 9,10 Particularly the anterior reach portion demonstrates high activation of the vastus medialis and lateralis. 11 The YBT-LQ has not been studied preoperatively in an ACL-R population to date.…”
Section: Introductionmentioning
confidence: 99%
“…The Y-Balance Test -Lower Quarter (YBT-LQ) is one of the functional tools used to measure single limb performance and neuromuscular control and has been studied in individuals with ACL-R. 9,10 The YBT-LQ requires an individual to load on a single leg and squat while reaching with the contralateral limb. This test not only measures neuromuscular control but has also been correlated to quadriceps and hip strength.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while the motor task used to measure dynamic balance is important, the measurement should be performed safely without engendering any feeling of fear. While the vertical drop jump and single-leg hop are often performed in clinical evaluation after ACL reconstruction surgery [9,10], this method affords a high risk for patients with no sports experience and those in the early phase after surgery on the knee joint. Thus, it would be useful to identify a motor task that can be safely performed by a wider range of subjects.…”
mentioning
confidence: 99%
“…We have shown that there are measurable functional deficits in athletes following surgical anterior cruciate ligament reconstructions after return to sport that are sustained up to 11 months after surgery. 13 While athletes may be prepared to begin sports-specific training for practice and competition, they typically demonstrate lingering deficits, that are not self-perceived and limit their potential for safe integration into full competition. Time will tell if there is an increase in reinjury occurrences in NFL athletes who sustained an injury in the past but were not fully rehabilitated during the Lockout.…”
mentioning
confidence: 99%